2020
DOI: 10.1111/camh.12435
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐focused cognitive behavioral therapy for children and youth in low and middle‐income countries: A systematic review

Abstract: Background Trauma‐focused cognitive behavioral therapy (TF‐CBT) has been identified as a gold standard treatment for childhood posttraumatic stress disorder (PTSD) in Western countries. More recently, TF‐CBT has emerged in the literature as an area of interest for children and youth affected by conflict and war in low‐ and middle‐income countries (LMIC). Methods The present systematic review assesses the current evidence base of TF‐CBT for children and youth in LMIC, with a focus on conflict‐affected countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Although interventions focused on reducing internalized stigma are nascent, there is promising evidence in support of psychoeducation (such as addressing gender equity and rape myths in post‐rape counselling) and cognitive–behavioural interventions to modify self‐stigmatizing beliefs (Alonso et al, 2019). Apart from the potential impact on internalized stigma, cognitive interventions may also address the underlying factors that increase risk of rape stigma, namely, childhood trauma (Thomas et al, 2020). Apart from reducing stigma, there is also good evidence to support the use of cognitive–behavioural therapy/cognitive processing therapy (CBT/CPT) interventions in rape survivors, and trauma‐focused CBT interventions (CBT/CPT) have been shown to accelerate recovery in rape survivors who have acute stress disorder (ASD) (Lomax & Meyrick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although interventions focused on reducing internalized stigma are nascent, there is promising evidence in support of psychoeducation (such as addressing gender equity and rape myths in post‐rape counselling) and cognitive–behavioural interventions to modify self‐stigmatizing beliefs (Alonso et al, 2019). Apart from the potential impact on internalized stigma, cognitive interventions may also address the underlying factors that increase risk of rape stigma, namely, childhood trauma (Thomas et al, 2020). Apart from reducing stigma, there is also good evidence to support the use of cognitive–behavioural therapy/cognitive processing therapy (CBT/CPT) interventions in rape survivors, and trauma‐focused CBT interventions (CBT/CPT) have been shown to accelerate recovery in rape survivors who have acute stress disorder (ASD) (Lomax & Meyrick, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from a subset of PACTS patients over the course of 9 years (2013-2021) revealed that youths receiving TF-CBT saw significant PTSD symptom improvements. Our effectiveness findings add to the robust evidence base establishing TF-CBT's effectiveness for diverse and underresourced youth experiencing significant social stressors and ongoing adversity (Dorsey et al, 2017;Orengo-Aguayo et al, 2022;Patel et al, 2022;Thomas et al, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…Continuing longer-term psychological work to finish addressing issues identified in the mind-body formulation (e.g., addressing illness-promoting psychological processes with a CBT intervention, or addressing unresolved loss or trauma with a trauma-focused intervention such as eye-movement desensitization, trauma-focused CBT, radical exposure tapping, or accelerated resolution therapy) 96–99 …”
Section: Step 7: Taking the Program Home To Maintain Resilience And P...mentioning
confidence: 99%